Efektivitas Model Pembelajaran Poblem Based Learning dan Realtime Feedback terhadap Pemahaman Siswa pada Topik Trigonomteri Segitiga Siku-Siku - Zahrotun, Siti; Nindiasari, Hepsi (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model integrated with teacher feedback in improving students’ understanding of the topic of trigonometry in right triangles. Due to students’ difficulties in comprehending the abstract nature of right triangle trigonometry and memorizing formulas, an innovative learning model is required to facilitate their understanding. This model also provides opportunities for students to practice problem-solving skills in real-life contexts, fostering critical thinking abilities.The results indicate that the PBL model, combined with teacher feedback during the learning process, produced better outcomes, as evidenced by cognitive test measurements. The experimental method used in this study was a one-group pre-test post-test design conducted quantitatively. Data were collected from a population of Grade X students at a high school in Serang City. The study employed test instruments consisting of multiple-choice and essay questions for data collection, which were analyzed using the non parametric paired sample t-test method.The analysis showed a significant improvement in the average scores, with post-test scores being higher than pre-test scores. It can be concluded that the implementation of the Problem-Based Learning model, integrated with teacher feedback, effectively enhances students’ understanding of the topic.